Emerging Context Market and Context-Aware Services - Stanoevska-Slabeva, Katarina; Wozniak, Thomas; Mannweiler, Christian; Hoffend, Isabella; Schotten, Hans (My University, 2010)
Context-aware services, such as location-based services, augmented reality applications, smart enterprise or assisted living applications, etc., constitute a cornerstone of the Future Internet. One important part of such applications is context information that describes the situation in which users consume the service. While earlier context referred mainly to location information provided by network operators, today new providers of context are emerging on the market together with a new context ecosystem. Based on in-depth case studies of emerging context providers conducted in the C-Cast project, this paper describes the emerging context market and ecosystem.